2021
DOI: 10.1108/jmtm-09-2020-0345
|View full text |Cite
|
Sign up to set email alerts
|

Does rational culture matter in the relationship between lean manufacturing practices and operational productivity?

Abstract: PurposeThis paper aims to examine the role of rational culture in the relationship between lean manufacturing practices and operational productivity in the machinery and equipment industry.Design/methodology/approachThis study uses a cross-sectional quantitative approach to conduct the research. Using an online survey questionnaire, 118 responses were collected. SPSS was used to assess validity, reliability and hypothesis testing of the study variables. Hierarchical regression analysis was employed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…This is resulted to work interruption. However, Ong et al (2021) explained that productivity can help organization survive the competition and it is also significant factor that generate revenue to organization which considered as a part of operational turnaround (Tikici et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This is resulted to work interruption. However, Ong et al (2021) explained that productivity can help organization survive the competition and it is also significant factor that generate revenue to organization which considered as a part of operational turnaround (Tikici et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Lean practices such as quick setup and quality control have been found to be significantly related to operational productivity. A study conducted in the machinery and equipment industry found that a rational culture could enhance the effects of lean manufacturing practices on operational productivity [15].…”
Section: Lean Manufacturing and Productivitymentioning
confidence: 99%
“…The main objective of lean production is to produce high-quality products with fewer expenditures and a shorter time span (Ong et al , 2021). Different manufacturing and service organizations are applying lean production systems and tools to sustain their competitive advantage.…”
Section: Literature Reviewmentioning
confidence: 99%